Implementation of Law and Actualization of Human Rights for Persons with Disabilities from Sexual Violence in Indonesia - Muhshonah, Muhshonah; Amrillah, Mohamad Yusfi; Maskur, Ali (Fakultas Hukum Dehasen, 2023)
Currently, sexual violence against women with disabilities often occurs. The lack of legal protection for women with disabilities means that they always experience discrimination from various parties. In the eyes of society, people with disabilities are looked down upon as people who need to be pitied, and in Indonesia itself, they live in a vulnerable environment due to restrictions, obstacles, and difficulties, and their rights are not properly fulfilled. The law itself regulates the protection rights of persons with disabilities, namely Law No. 18 of 2016.Often, people with disabilities become victims of violent acts, which makes it difficult for the perpetrators to be prosecuted by the police or prosecutors. The government itself has not fully provided special facilities to people with disabilities who are in conflict with the law. The government should make clear and firm regulations for people with disabilities who are victims of sexual harassment in order to guarantee protection for people with disabilities with clear laws